A face recognition system using template matching and neural network classifier - Muhammad Firdaus, Hashim; Puteh, Saad; Mohamed Rizon, Mohamed Juhari; Shahrul Nizam, Yaakob (Kolej Universiti Kejuruteraan Utara Malaysia, 2009)
Organized by Kolej Universiti Kejuruteraan Utara Malaysia (KUKUM), 14th - 15th May 2005 at Putra Palace Hotel, Kangar, Perlis.